CLINICAL ANALYSIS OF RISK FACTORS FOR BREAST CANCER IN YOUNG WOMEN - M. S. Salomov; Z. M. Zokirova (Web of Journals Publishing, 2025)
Breast cancer in young women is more often aggressive but less common than in older women. Characteristic features include more aggressive tumor types, difficult diagnosis due to high breast tissue density, and frequent detection of the disease at late stages. Risk factors include genetic predisposition, early onset of menstruation, late first birth, and lack of breastfeeding.
Keywords: Cancer, breast cancer, cancer in young women.